Leveraging Small Group Discussion Technique with Kahoot Application for Maharah Qira’ah Learning Design in Higher Education - Syaifudin, Moh.; Ainin, Moh.; Rosyidi, Abdul Wahab; Arifin, Ahmad; Syarifaturrahmatullah, Syarifaturrahmatullah (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2024)
Technological advances changes the students' learning styles, especially Arabic language learning. This phenomenon requires teachers to create a suitable learning designs. This article aimed to develop a learning design for Arabic reading skills by using the Kahoot application based on small group discussions. R&D (Research and Development) type was used with the ADDIE model which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection instruments in this research were observation, interviews, questionnaires, and documentation. The primary data was obtained from respondents through questionnaires and interviews. Meanwhile, the secondary data was obtained from books, scientific journals, and internet sources relevant to this research. Likert scale was used as data analysis. The results showed that the validity of the learning planning design based on the material validator obtained 4,75 as the results which referred to very good criteria. Meanwhile, media validators obtained 4,6 which referred to very good category. Thus, the design validators obtained 4,8 which referred to very good category, and 2) The results of student responses obtained 82% with good criteria. Based on this result, Small Group Discussion Techniques with Kahoot application is suitable for arabic learning design in higher education.